2019
DOI: 10.1021/acsaelm.9b00489
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Effects of Near-Field Enhancement-Induced Excitation and Surface Plasmon-Coupled Emission of Elongated Gold Nanocrystals on Fluorescence Enhancement and the Applications in PLEDs

Abstract: Localized surface plasmon resonance (LSPR) field enhancement effects of noble metallic nanoparticles can be exploited to enhance the performance of diverse luminescent materials and devices, in which the spectral proximity plays an important role in increasing near-field enhancement-induced excitation (NFEE) and surface plasmon-coupled emission (SPCE) efficiencies. In this work, we propose a scheme simultaneously utilizing the transversal and longitudinal SPR bands of elongated gold nanocrystals to match with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…10 Benefiting from the unique enhancement of light absorption induced by the LSPR effect, noble metal NPs, especially Au NPs have been applied to the field of photoelectric detection. 11 Li et al found that light absorption of the Au−MoS 2 heterojunction could be significantly enhanced due to the LSPR effect, and the photoresponsivity was as high as 22.3 A/ W. 12 significantly increased on account of the plasmonic effect of Au NPs. 13,14 In addition, Au NPs exhibit strong extinction spectra.…”
Section: ■ Introductionmentioning
confidence: 99%
“…10 Benefiting from the unique enhancement of light absorption induced by the LSPR effect, noble metal NPs, especially Au NPs have been applied to the field of photoelectric detection. 11 Li et al found that light absorption of the Au−MoS 2 heterojunction could be significantly enhanced due to the LSPR effect, and the photoresponsivity was as high as 22.3 A/ W. 12 significantly increased on account of the plasmonic effect of Au NPs. 13,14 In addition, Au NPs exhibit strong extinction spectra.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In SPCE technology, the prism-based SPCE device is most widely utilized and has been applied in multiple analytical and bioanalytical assays, e.g., molecular sensing, immunoassay, and DNA sensing [10,23,28]. In this equipment, fluorescent molecules are located on the thin metal film, which is then attached to the prism with a RI matching fluid.…”
Section: Spcei Based On Prismmentioning
confidence: 99%
“…However, there is a great demand to achieve higher sensitivity and selectivity with the rapid development of life science. Recently, a surface-enhanced fluorescence technique, referred to as surface plasmon-coupled emission (SPCE), has been widely investigated [7][8][9][10][11]. The high collection efficiency, due to the directed radiation, greatly improves the sensitivity of SPCE.…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, research efforts have been devoted to synergize PEF and SPCE into a single hybrid platform. [7][8][9][10][11]14 Generally, the enhancement factor of SPCE substrate is 5−10-fold as compared to traditional luminescence. [7][8][9][10][11]15 Lakowicz and coworkers have demonstrated the significance of silver (Ag) NPs spacer layer engineering on SPCE platform to further augment the enhancement to 60-fold.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11]14 Generally, the enhancement factor of SPCE substrate is 5−10-fold as compared to traditional luminescence. [7][8][9][10][11]15 Lakowicz and coworkers have demonstrated the significance of silver (Ag) NPs spacer layer engineering on SPCE platform to further augment the enhancement to 60-fold. 15 With this as a preliminary step for combining PEF and SPCE, diverse nanoarchitectures have been explored to further augment the SPCE enhancements.…”
Section: Introductionmentioning
confidence: 99%